2000
DOI: 10.2166/wst.2000.0376
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of arsenic rejection considering affinity and steric hindrance effect in nanofiltration membranes

Abstract: Rejection characteristics of arsenic compounds such as arsenite, dimethyl arsinic acid, and arsenate were examined regarding the effect of pH change in nanofiltration. Rejection mechanism of arsenic compounds was explained by comparing experimental rejection with calculation of the Extended Nernst-Planck model coupled with steric hindrance model. Nanofiltration membranes of the same material show similar rejection characteristics of arsenic compounds in different species. Steric hindrance and electrostatic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 6 publications
2
11
0
1
Order By: Relevance
“…This may be attributed to a change in the speciation of cyanide, as well as a change of zeta potential of negatively charged membranes with a change in the pH levels. Similar observations have been made by some researchers (Oh et al, 2000;Siedel et al, 2001;Urase et al, 1998) in connection with arsenic separation. Figure 5 shows the variations of membrane charge density (X d ) with a change of pH, where membrane charge densities were computed from the linearized transport model.…”
Section: Experimental Methodssupporting
confidence: 89%
“…This may be attributed to a change in the speciation of cyanide, as well as a change of zeta potential of negatively charged membranes with a change in the pH levels. Similar observations have been made by some researchers (Oh et al, 2000;Siedel et al, 2001;Urase et al, 1998) in connection with arsenic separation. Figure 5 shows the variations of membrane charge density (X d ) with a change of pH, where membrane charge densities were computed from the linearized transport model.…”
Section: Experimental Methodssupporting
confidence: 89%
“…To exploit the ability of membrane filtration to remove As(V), several researchers have suggested that a pretreatment step that oxidizes the As(III) to As(V) would improve the performance of membrane filtration (Seidel et al, 2001; Oh et al, 2000; Kartinen & Martin, 1995), but the authors of the current research are not aware of any investigations that have tested this hypothesis. Oxidation of arsenic using manganese dioxide (MnO 2 ) has been explored by other researchers (Manning et al, 2002; Ghurye & Clifford, 2001), but use of this as an arsenic oxidation step has never been combined with membrane filtration.…”
mentioning
confidence: 99%
“…As with charged organic xenobiotics metals and heavy metals are mainly removed through the Donnan exclusion mechanism where the metal ion with the same charge as the membrane has a retention higher than 80% (Raff and Wilken 1999;Favre-Reguillon et al 2003) due to charge repulsion (Raff and Wilken 1999;Oh et al 2000;Seidel et al 2001;Choo et al 2002;Favre-Reguillon et al 2008). Metal speciation study is therefore important to understand the rejection mechanisms not only due to different charges the metal species carry but also due to different species the metal can form for example with carbonates and NOM, which affects its size and therefore its retention.…”
Section: Charge Repulsionmentioning
confidence: 99%